ChemInform Abstract: Regioselective Allene Hydrosilylation Catalyzed by N‐Heterocyclic Carbene Complexes of Nickel and Palladium. Issue 10 (11th March 2014) - Miller, Zachary D.; Li, Wei; Belderrain, Tomas R.; Montgomery, John
Abstract Regioselective hydrosilylation of allenes strictly depends on the choice of metal.